IPF Respiratory Symptoms Management — Current Evidence - Janowiak, Piotr; Szymanowska-Narloch, Amelia; Siemińska, Alicja (Frontiers in Medicine, 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive, chronic disease of the lungs which is characterized by heavy symptom burden, especially in the last year of life. Despite recently established anti-fibrotic treatment IPF prognosis is one of the worst among interstitial lung diseases. In this review available evidence regarding pharmacological and nonpharmacological management of the main IPF symptoms, dyspnea and cough, is presented.